Gambaran Residu Pestisida Organofosfat Makanan Lalapan Kubis (Brassica Oleacea) Pada Pedagang - Hartami, Dwi Tyas; Yusananta, Prayudhy; Murwanto, Bambang (Universitas Malahayati Bandar Lampung, 2024)
Background : Food poisoning is one of the health problems in Indonesia. Most of this is caused by contamination of food, such as vegetables and fruit as horticultural crops. The contaminants that are usually present in these foods are usually toxic residues as pest killing agents in these materials. The pesticides used include those from the organophosphate group, which is up to 40% of the other groups. The organophosphate group is Dimethiot, Diazinon, Fenthion, Chlorpyrifos and Prefenofos. It is estimated that the prevalence of organophosphate poisoning cases throughout the world reaches one million cases per year, out of 2 million cases of poisoning and 200,000 deaths worldwide.Purpose : This research is to determine the residue of organophosphate group pesticides in cabbage fresh vegetables based on storage, processing and presentation in the city of Bandar Lampung. This type of research is quantitative with a descriptive approach.Methods : This type of research is quantitative and observational with a descriptive approach, to determine organophosphate pesticide residues in cabbage fresh vegetables. The research location is at the Agricultural Product Quality Testing Laboratory, Lampung University. Samples were taken from cabbage salad traders in the Way Halim Permai area of Bandar Lampung City in March-April 2023. The sampling technique was purposive sampling (nonprobably sampling), divided into two sources, namely home traders and non-home traders.Results : This research shows that cabbage contains residues of organophosphate pesticides with the active ingredients Dimethiot, Diazinon, Fenthion, Chlorpyrifos and Prefenofos. Meanwhile, the highest result from the test results was the active ingredient Fenthion, namely 0.8607 mg/kg and the lowest result was the active ingredient Chlorpyrifos, amounting to 0.0191 mg/kg and still below the Maximum Threshold. There are differences in residue according to storage, processing and presentation, and the best (low) is processing.Conclution : The presence of organophosphate group pesticides in cabbage samples with the active ingredients Dimethoat, Diazinon, Fenthion, Chlorpyrifos, and Prefenofos. However, the highest residue is the active ingredient Fenthion at 0.8607 mg/kg and the lowest is the active ingredient Chlorpyrifos, at 0.0191 mg/kg, and is still below the Maximum Residue Limit. Keywords: Pesticide, Cabbage, Residue, Poisoning.